Implementation of Personal Branding in the Career Development of Gen Z Employees - Fajar Syaifurrochman; Ahmad Munajim (Advances In Social Humanities Research, 2026)
The development of digital transformation has altered career development patterns in the modern workplace. Generation Z, as a new productive age group, possesses characteristics closely related to technology, social media, and personal branding culture. This study aims to analyze the implementation of personal branding in the career development of Generation Z employees within a professional workplace.  A qualitative approach with descriptive methods was employed. Data collection techniques included in-depth interviews, observations, and documentation involving several Generation Z employees from service and digital creative sector companies. The results indicate that personal branding is an important strategy for building a professional identity, increasing self-confidence, expanding professional networks, and opening up career development opportunities. Professional social media platforms such as LinkedIn and Instagram serve as the primary means for shaping the professional image of Gen Z employees. However, personal branding implementation also faces challenges, including digital identity consistency, social pressure, and the need to adapt to organizational culture. This study concludes that personal branding significantly contributes to supporting the career development of Generation Z employees in the digital era. Therefore, companies should provide support through self-development training and professional digital literacy.